2012
DOI: 10.1017/s0007114512002577
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of protein adequacy in developing countries: quality matters

Abstract: Dietary protein and amino acid requirement recommendations for normal "healthy" children and adults have varied considerably with 2007 FAO/WHO protein requirement estimates for children lower, but dietary essential AA requirements for adults more than doubled. Requirement estimates as presented do not account for common living conditions, which are prevalent in developing countries such as energy deficit, infection burden and added functional demands for protein and AAs. This study examined the effect of adjus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
79
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 115 publications
(84 citation statements)
references
References 40 publications
(56 reference statements)
3
79
1
Order By: Relevance
“…However, stunting is a form of protein-energy malnutrition [63], and protein deficiency has been shown to be a leading nutritional predictor of stunting [64]. Adjusting for maternal protein intake is therefore likely to capture much of the effect of nutritional status on stunting, with the assumption that children are exposed to similar protein levels as their mothers.…”
Section: Discussionmentioning
confidence: 99%
“…However, stunting is a form of protein-energy malnutrition [63], and protein deficiency has been shown to be a leading nutritional predictor of stunting [64]. Adjusting for maternal protein intake is therefore likely to capture much of the effect of nutritional status on stunting, with the assumption that children are exposed to similar protein levels as their mothers.…”
Section: Discussionmentioning
confidence: 99%
“…Using national data from 180 countries, Ghosh and colleagues showed that protein quality, which takes into account essential amino acid composition, digestibility, energy deficit, and infections, was associated with the prevalence of stunting [46]. Millions of children subsist on staple foods that are poor sources of essential amino acids, such as cassava and maize.…”
Section: Recent Studies On Protein Quality Essential Amino Acids Anmentioning
confidence: 99%
“…Studies have indicated that the prevalence of stunting is highly correlated with total protein and utilizable protein intake in certain regions, particularly Sub-Saharan Africa and South Asia [4, 5]. However, there is limited evidence suggesting that protein supplementation via interventions improves linear growth in children in developing countries with a high prevalence of stunting.…”
Section: Introductionmentioning
confidence: 99%